Pelatihan Komputer MS Office Bagi Remaja Karang Taruna RW 010 Rorotan - Nurmala Dewi Qadarsih; Maimunah Maimunah (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
The purpose of this community service activity is to help youth youth groups to develop skills in operating and running computers, especially in Microsoft office (word, excel, and power point). The targets of this community service activity are youth youth groups at RW 010 Rorotan in North Jakarta with a total of 6 trainees. The training is carried out in three stages of activity consisting of observation, training implementation, as well as evaluation and monitoring. At the observation stage, an analysis of the problems and needs of youth youth is carried out to operate Microsoft office which includes word, excel, and power point. At the implementation stage of the activity, a direct presentation of the material and practice was given. At the evaluation and monitoring stage, direct evaluation and monitoring are carried out to see the abilities that have been achieved by youth youth in operating Microsoft office. Based on the results of the training and monitoring of activities, it was found that Microsoft office computer training activities are very relevant to improve skills and broader knowledge of youth youth groups in RW 010.